2022
DOI: 10.3390/su14127463
|View full text |Cite
|
Sign up to set email alerts
|

Shall the Wild Boar Pass? A Genetically Assessed Ecological Corridor in the Geneva Region

Abstract: Landscape fragmentation caused by road infrastructures represents a major threat to the genetic diversity of a region. The resulting genetic isolation between subpopulations may lead to consanguinity, and consequently to population collapse and extinction. However, the construction of wildlife crossings can help maintain connectivity. In the present paper, we evaluated the genetic spatial structuring of populations of wild boars (Sus scrofa) in three areas of the Geneva region connected by an ecological corrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
2
1
0
Order By: Relevance
“…However, the observed heterozygosity value (Ho = 0.623) was close to that quantified in the earlier study on wild boars (Ho = 0.627), despite the fact that the sample size in the current study was four times greater. Similar levels of Ho have also been detected in Bulgaria [ 18 ], Portugal [ 19 ], Croatia [ 39 ] and the Geneva region [ 25 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, the observed heterozygosity value (Ho = 0.623) was close to that quantified in the earlier study on wild boars (Ho = 0.627), despite the fact that the sample size in the current study was four times greater. Similar levels of Ho have also been detected in Bulgaria [ 18 ], Portugal [ 19 ], Croatia [ 39 ] and the Geneva region [ 25 ].…”
Section: Discussionsupporting
confidence: 71%
“…In contrast, one genetic cluster was confirmed in the Lithuanian wild boar population before ASF [ 24 ] and two genetic groups were identified in wild boar populations in the Carpathian Basin [ 23 ]. The homogenous genetic structure was also confirmed in a recent study that showed the clustering of all individuals into a single genetic group in three areas of the Geneva region connected by an ecological corridor [ 25 ]. The contrasting findings in the present study compared with previous studies may be related to the geographic scale of the study, the use of different markers and the sample size.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation